2007
DOI: 10.1177/0961203306075741
|View full text |Cite
|
Sign up to set email alerts
|

Reduced placental growth and hCG secretion in vitro induced by antiphospholipid antibodies but not by anti-Ro or anti-La: studies on sera from women with SLE/PAPS

Abstract: Systemic lupus erythematosus (SLE) and primary anti-phospholipid syndrome (PAPS) are autoimmune diseases causing recurrent pregnancy loss. We hypothesized that anti-phospholipid antibodies (aPL), but not anti-Ro and anti-La antibodies, might have a role through direct placental damage. We cultured human placental explants in sera from women with SLE/PAPS with different antibodies. These sera were found to reduce placental growth and increase trophoblastic apoptosis. No effect was found on estradiol or progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In general, outside of the context of heart injury, anti-SSA/Ro and anti-SSB/La exposure is not clearly associated with growth development. This observation is also supported by the lack of reduced placenta growth when exposed to anti-SSA/Ro and anti-SSB/La [12].…”
Section: Pregnancy Outcomes In Women With Systemic Lupus Erythematosussupporting
confidence: 66%
“…In general, outside of the context of heart injury, anti-SSA/Ro and anti-SSB/La exposure is not clearly associated with growth development. This observation is also supported by the lack of reduced placenta growth when exposed to anti-SSA/Ro and anti-SSB/La [12].…”
Section: Pregnancy Outcomes In Women With Systemic Lupus Erythematosussupporting
confidence: 66%
“…Apoptosis in the trophoblasts was observed after passive 27–29 or active immunization in experimental animals 30–32 . Other studies also have indicated that the antibodies listed above stimulated apoptosis in human trophoblast in vitro 33–36 . In contrast, there have been no animal studies regarding aPE and anti‐FXII.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have examined the effects of polyclonal aPL isolated from patient sera, as well as murine monoclonal aPL on placental explants or cell lines (Yacobi et al 2002, Ornoy et al 2003, Bose et al 2004, Schwartz et al 2007. Studies examining the mechanism of reduced migration showed that aPL mediate this effect possibly through the downregulation of interleukin 6 (IL6; Mulla et al 2010) and the up-reguation of TIMP2 (Albert et al 2014), all independently of Toll-like receptor 4 (TLR4).…”
Section: Trophoblast Proliferation Migration and Invasionmentioning
confidence: 99%
“…Several in vitro studies have reported an increase in trophoblast death in response to aPL using either term trophoblasts or first-trimester trophoblasts (Di Simone et al 2001, Yacobi et al 2002, Ornoy et al 2003, Schwartz et al 2007, Chen et al 2009, Mulla et al 2009). Cytotrophoblasts isolated from term placentae (Di Simone et al 2001 have been shown to alter their expression of the apoptotic regulators Bax and Bcl2 in response to aPL, but without overt signs of cell death (Di Simone et al 2006).…”
Section: Trophoblast Deathmentioning
confidence: 99%
See 1 more Smart Citation